PEMBUATAN HARDBOARD DARI SERAT ALTERNATIF MENGGUNAKAN LIGNIN ALAMINYA DAN TANIN FORMALDEHIDA SEBAGAI PEREKAT - Dian Anggraini Indrawan; Han Roliadi; Rossi Margareth Tampubolon; Mohamad Iqbal; Lisna Efiyanti (Center for Pulp and Paper, 2015)
The most numerous uses of hardboard are for sound-deadening barrier, insulation wall, furniture, part of electronic appliances, and vehicle interior.Nowadays, in Indonesia the availability of natural-forest woods (the conventional ligno-cellulosic fibrous raw material) for fiberboard manufacture becomes limited and scarce. Thus, non-wood alternative fibers should be considered as raw material for fiber board. In this study, experiment was done using alternative fibers which were Saccharum spontaneum grasses (SSG), empty oil-palm bunches (EOPB), and bamboo. The pulping and mat forming employed consecutively an open-hot soda semi-chemical process and wet-forming process. The additives for hardboard forming comprised wax emulsion and tannin formaldehyde (TF) adhesive.Alkali consumption in the pulping of alternative fibers (SSG, EOPB, and bamboo) for hardboard ranged about 88-99% (regarded as quite high, near 100%). SSG was the most prospective for hardboard, followed by consecutively EOPB and bamboo. Also, physical-strength properties of hardboard from SSG satisfied the JIS and ISO requirement the most. The prospective results of fiberboard manufacture from the alternative fiber materials will expectedly lessen the dependency on naturalforest woods thereby sustaining the natural resources, and alleviating environment concerns. The high alkali consumption and wet-forming implementation hinted that this fiberboard-manufacturing experiment is more suitable for small-medium scale endeavor (SME). Keywords: hardboard, alternative ligno-cellulosic fiber materials, prospective results, sustaining natural resources, small-to-medium scale endeavor (SME)ABSTRAKHardboard banyak digunakan antara lain untuk bahan peredam suara, dinding penyekat, mebel, bagian dari peralatan elektronik dan interior kendaraan. Di Indonesia, ketersediaan kayu hutan alam (bahan baku serat berligno-selulosa konvensional) untuk pembuatan papan serat di Indonesia semakin terbatas dan langka. Oleh karena itu bahan serat alternatif harus dipertimbangkan sebagai bahan baku papan serat. Dalam penelitian ini dilakukan percobaan pembuatan papan serat (hardboard) dari bahan serat alternatif, yaitu rumput gelagah (RG), tandan kosong kelapa sawit (TKKS) dan bambu. Pengolahan pulp (pulping) dan pembentukan lembaran untuk papan serat menggunakan proses semi-kimia soda panas terbuka dengan pembentukan cara basah (wet process). Bahan aditif yang digunakan adalah emulsi lilin dan perekat tanin formaldehida (TF) Konsumsi alkali pada pulping adalah 88-99% (dianggap cukup tinggi, mendekati 100%). RG paling berprospek untuk hardboard diikuti oleh TKKS dan bambu, dan sifat fisik-kekuatan hardboard dari RG paling banyak memenuhi persyaratan JIS dan ISO. Hasil prospektif pemanfaatan serat alternatif untuk papan serat diharapkan bermanfaat mengurangi ketergantungan pada kayu hutan alam sehingga ikut melestarikan sumber daya alam. Tingginya konsumsi alkali dan penerapan cara basah berindikasi bahwa pengolahan papan serat ini lebih sesuai untuk usaha kecil menengah (UKM).Kata kunci: hardboard, bahan baku serat alternatif, hasil prospektif, melestarikan sumber daya alam, usaha kecil menengah (UKM)